Da construção à montagem - Porfirio Valadares de Andrade (2012)
This work has as its goal the investigation and collection of the changes that traditional carpentry has been through since the introduction of Medium Density Fiberboard (MDF) in Brazil, changes that definitely altered carpenters way of work, drawing their labor out from the constructions world to insert it in the assemblys. The collection of data begins with the firsts productions of wood furniture in brazilian lands and continues to investigate the evolution of woodwork techniques applied in different types and subtypes of furniture here produced through out history. To better understand the motivations that led to the changes infurniture construction techniques, it was also investigated the characteristics of in natura wood that prompt it. The exchange of carpentrys basic raw material, represented by the gradual timber substitution for the panels therefore derived is led by these panelscharacteristics study and the impact that it promoted as it appeared, all ending in MDF, technological innovation with the potential not just to insert the assembly and pre-fabrication in carpentrys universe but also to promote the rising of a new kind of professional that will compete with them. After this point the post MDF era was studied, witch unveils a newoutlook that still baffles traditional carpenters and, finally, were investigated the new work fields that can contribute to prevent the full extinction of their craft.